Structure and magnetic properties of multi-walled carbon nanotubes modified with iron - Grechnev, G.E.; Scharff, P.; Ritter, U.; Grybova, M.I.; Prylutskyy, Yu.I.; Matzui, L.Yu.; Panfilov, A.S.; Fedorchenko, A.V.; Desnenko, V.A.; Kolesnichenko, Yu.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
Magnetic properties of multi-walled carbon nanotubes modified with iron (MWCNT+Fe) are studied in detail in the temperature range 4.2–300 K. Carbon encapsulated Fe nanoparticles were obtained using chemical vapor deposition method. The low-temperature SQUID magnetization measurements are supplemented by structural investigations with thermogravimetric (TG) analysis, transmission electron microscopy (TEM), x-ray diffraction spectroscopy (XRD), and scanning electron microscopy (SEM). The magnetic susceptibility of MWCNT+Fe was also studied above room temperature to provide a complete picture of magnetic phase transitions.